2010
DOI: 10.1186/1749-8090-5-31
|View full text |Cite
|
Sign up to set email alerts
|

Off-pump versus on-pump coronary artery bypass grafting in acute coronary syndrome: a clinical analysis

Abstract: BackgroundAlthough off-pump coronary artery bypass (OPCAB) surgery has many beneficial effects compared with on-pump surgery, switch to on-pump surgery has significantly higher risks of operative mortality. Benefits of OPCAB over on-pump surgery strategies concerning myocardial revascularization are still debatable. We have aimed to develop an "algorithm of off-pump surgical strategy" on preventing conversion to on-pump. This clinical study reports our clinical outcome of OPCAB in patients with acute coronary … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
15
0

Year Published

2011
2011
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(16 citation statements)
references
References 21 publications
1
15
0
Order By: Relevance
“…In general, it is known that the duration of surgery is directly connected with the duration of CBP (17) . As for complication, pain was the most frequent in both groups under analysis, which can be explained by the extent of the tissue trauma patients were submitted to during cardiac surgeries.…”
Section: Discussionmentioning
confidence: 99%
“…In general, it is known that the duration of surgery is directly connected with the duration of CBP (17) . As for complication, pain was the most frequent in both groups under analysis, which can be explained by the extent of the tissue trauma patients were submitted to during cardiac surgeries.…”
Section: Discussionmentioning
confidence: 99%
“…In two studies, mortality was lower in off-pump vs. on-pump procedures (5% vs. 24%, P = 0.015 and 3.5% vs. 5.4%, P = 0.690) [53,54] . Additionally, a European study with a cohort of 624 patients demonstrated that stratification and preselection of patients, as well as the timing of the intervention, are crucial considerations for ensuring that only appropriate candidates undergo and derive benefits from the procedure [55] .…”
Section: Off-pump Cabgmentioning
confidence: 99%
“…There has been some suggestions, however, that even in higher-risk patients, early CABG is associated with very low in-hospital mortality and, therefore, could be considered in appropriate situations [8] . For OPCABG, data suggest that patients taken to the operating room within 6 h from the onset of chest pain are more suitable for off-pump surgery and have a low incidence of conversion to on-pump CABG, which, as mentioned above, carries severe risks and consequences [54] .…”
Section: Timing Of Surgical Revascularizationmentioning
confidence: 99%
See 1 more Smart Citation
“…In general, it is known that the time of surgery is directly related to CPB time (19) . In some studies (17,20) in which there was statistically significant difference, the CPB time was lower in patients without excess of weight and overweight and higher in obese patients.…”
mentioning
confidence: 99%